Late embolectomy and thrombectomy - Gastambide, Carmelo; Croci, Fabio; Calleriza, Fernando; Terra, Eneas; Ormaechea, Carlos (Cirugía del Uruguay, 1983)
. Five cases of acute arterial embolism that had !'volved for 30 hours to 12 days are presented. Patients have had severe cardiac disease. Surgery a<'hieved good results. The inferior limb was affected in four cases, the arm was in the other one. The importance of surgical treatment without taking into account the evolution period is pointed out. Factors that influence over the pathological course and the prognosis are discussed.